Spark plasma sintering of mullite: Relation between microstructure, properties and spark plasma sintering (SPS) parameters. Issue 5 (June 2015) - Ghahremani, D.; Ebadzadeh, T.; Maghsodipour, A.
Abstract: The spark plasma sintering (SPS) of mullite powder ( D 50 =3.29 μm) was investigated. The SPS parameters such as the dwell temperature, applied external pressure, and dwell time were varied. The sinterability of mullite increases with increase in the dwell temperature, dwell time and applied external pressure. The influence of porosity on mechanical properties (hardness, and fracture toughness) of mullite prepared by SPS is measured. Pulsed DC current is found to play a dominant role in the densification of mullite and achieving near theoretical density. Hardness, and fracture toughness of near fully dense mullite are measured as 1256 HV, and 2.8 MPa m 1/2 respectively.